Syphilitic meningomyelitis presenting with visceral crisis: A case report. Issue 30 (July 2018) - Sun, Li; Zheng, Nannan; Yang, Yu; Zhang, Hai-Ning
Abstract: Rationale: We report a rare case of syphilitic meningomyelitis presenting with visceral crisis and possessing characteristic imaging findings. Patient concerns: The patient, a 50-year-old woman, complained of pain in the upper abdomen and back. She then developed numbness in both lower extremities and weakness in the left lower limb. Diagnosis: Magnetic resonance imaging (MRI) of the spinal cord revealed the candle guttering sign and irregular enhancement at the T6 level. Rapid plasma reagin test of the cerebrospinal fluid yielded a titer of 1:8. Thus, the patient was diagnosed with syphilitic meningomyelitis. Interventions: She was treated with ceftriaxone and dexamethasone after the failure of penicillin treatment. Outcomes: She could perform the activities of daily living, and her pain completely disappeared. Lessons: A patient with syphilitic meningomyelitis can present with visceral crisis caused by the involvement of the posterior nerve roots or the posterior horn, which usually occurs in patients with tabes dorsalis. Considering the non-specific symptoms and MRI features, we should be aware that abdominal pain may be a symptom of myelopathy, and syphilitic meningomyelitis ought to be taken into account in a patient with longitudinally extensive myelitis.